Miért fáj nekünk, magyaroknak már közel egy évszázad óta Trianon? - Kugler, József (Közép-Európai Közlemények, 2010)
The Trianon Peace Treaty that ended the World War I for Hungary placed the one-third of Hungarians outside the new national borders and made them take a new „minority‟ way of life. For a long period, it was part of the mainstream national policies in neighbouring countries to put the Hungarian ethnicity under a heavy pressure, for which, „forced migration‟, a set of administrative tools that made Hungarians leave their homeland en masse was a widely used. Each of the two major ethnic movements (in the years following World War I and II) resulted in a loss of about 400.000 migrants who left to Hungary and other countries. Thus, the history of the past century entailed tensions and conflicts that hinder the reconciliation and cooperation between the neighbouring states in the region, even though, most of them are members of the EU or aspiring for that.